Molecular Interventions for Developing Climate-Smart Crops: A Forage Perspective - Singhal, Rajesh Kumar; Ahmed, Shahid; Pandey, Saurabh; Chand, Subhash (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This edited book is collection of information on molecular interventions needed for climate-resilient forage crops. The main focus is to address the gap in the advanced scientific knowledge for the forage species. Agriculture is extremely vulnerable to climate, and even slight change in climatic factors such as temperature causes tremendous losses in yield potential. Forage crops are crucial in global food security and environmental sustainability and face several environmental challenges in field conditions. However, the research on forage crops is far-off compared to agricultural crops and causes a substantial gap in forage demand and productivity. Further, this gap is directly associated with animal health, reproduction, and productivity. Abiotic stresses mainly affect the plant's crucial processes, ultimately reducing the final yield. The problem of abiotic stresses is more frequent in forage crops as they are growing and cultivated in less productive soil and harsh conditions. This book discusses current aspects of crucial physiological, biochemical and molecular processes in forage crops, which are essential for forage crops improvement. The text's major focus is on the advanced technologies and approaches such as seed priming, bio-fortification, breeding, omics, transgenic and bioengineering of metabolic pathways in unique ways, which helps us develop innovative solutions for forage crops. This book covers all the crucial advance technologies, which help mitigate the abiotic stresses in forage crops. We believe that this book will initiate and introduce the readers to state-of-the-art developments and unique in this field of study. This book is of interest to teachers, researchers, climate change scientists, capacity builders, and policymakers. Also, the book serves as additional reading material for undergraduate and graduate students of agriculture, forestry, ecology, soil science, and environmental sciences. National and international agricultural scientists and policymakers will also find this a worthwhile read.
Chapter 1. Genetic and genomic resources of range grasses- status and future prospects -- Chapter 2. Forage genetic resources and scope for allele mining of abiotic stress tolerance -- Chapter 3. Breeding for developing higher productive tree-based forage under stress environments -- Chapter 4. Impact of Climate change on forage crop production with special emphasis on diseases and mitigation strategies through breeding and molecular approaches -- Chapter 5. Effect of nano-priming on maize under normal and stressful environment -- Chapter 6. Oxidative stress and antioxidant defense in mitigating abiotic stresses in forage crops: A physiological and biochemical perspective -- Chapter 7. Forage cropping under climate smart farming: a promising tool to ameliorate salinity threat in soils -- Chapter 8. Forage cultivation under challenging environment -- Chapter 9. Potentials and Opportunities of Agro-forestry Under Climate Change Scenario -- Chapter 10. Climate Change Impact on Forage Characteristics: An Appraisal for Livestock Production -- Chapter 11. Sustainable Use of Paddy Straw as Livestock Feed: A Climate Resilient Approach to Crop Residue Burning -- Chapter 12. Engineering Interventions for Climate Resilient Forage Production -- Chapter 13. Promotion of improved forage crop production technologies: Constraints and strategies with special reference to climate change. .
Keywords: Plant physiology; Stress (Physiology).; Plants; Microbial ecology; Plant Physiology; Plant Stress Responses; Microbial Ecology